Latin at the crossroads of identity : the evolution of linguistic nationalism in the Kingdom of Hungary - Almási, Gábor; Šubarić, Lav (Central and East European series, 2015)
From the late 18th century in the multi-ethnic Kingdom of Hungary, new language-based national identities came to dominate over those that had previously been constructed on legal, territorial, or historical basis. While the Hungarian language struggled to emancipate itself, the roles and functions of Latin (the official language until 1844) were changing dramatically. Latin held a different significance for varying segments of society, from being the essential part of an individual identity to representing an obstacle to "national survival"; from guaranteeing harmony between the different linguistic communities to hindering change, social and political justice. This pioneering volume aims to highlight the ways language debates about Latin and Hungarian contributed to the creation of new identities and ideologies in Central Europe. Contributors include Gábor Almási, Per Pippin Aspaas, Piroska Balogh, Henrik Hönich, László Kontler, István Margócsy, Alexander Maxwell, Ambrus Miskolczy, Levente Nagy, Nenad Ristović, Andrea Seidler, Teodora Shek Brnardić, Zvjezdana Sikirić Assouline, and Lav Šubarić.